A case of Chronic Thromboembolic Pulmonary Hypertension in association with Deep Vein Thrombosis and Pulmonary Embolism: A case report of a young female in Bangladesh (Bangladesh Heart Journal, 2023)
Chronic thromboembolic pulmonary hypertension (CTEPH) is classified as Group 4 Pulmonary Hypertension (PH) in current categorization by WHO. The initial suspicion with clinical presentation, then screening with imaging and confirmation with Right heart catheterization (RHC) are the steps of diagnostic algorithm for CTEPH. We report the case of a 35 years old female presented with progressive swelling of left lower limb for 2 months and shortness of breath for 1 and half months. Examination revealed respiratory rate 28 breaths/min, pitting edema of left leg, left parasternal heave and palpable P2. Doppler study of both lower limbs and Computed tomography pulmonary angiography (CTPA ) confirmed the diagnosis of deep vein thrombosis of left leg (DVT) and pulmonary embolism (PE), respectively. The echocardiography suggested presence of pulmonary hypertension. We approached the patient with conservative management and discharged her home, once she improved, with advice of life-long anticoagulation.Bangladesh Heart Journal 2023; 38(2): 143-147